(untitled) (Research, Society and Development, 2022)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease that is known to be associated with neuropsychiatric manifestations with a prevalence of 17 to 75% in patients with the disease. Catatonia has been described in the clinical spectrum of neuropsychiatric manifestations (NPM) of SLE. The aim of this study was to characterize, through a systematic review, the clinical manifestations and treatment of catatonia induced by Systemic Lupus Erythematosus (SLE). A systematic review of a case report and series was carried out using the descriptors “Systemic Lupus Erythematosus” and “Catatonia”, from 1977 to 2021, in the published Medline©, PubMed©, Lilacs©, Scielo© and EMBASE© databases. in Spanish, French, English and Portuguese. Of a total of 50 patients analyzed in the selected studies, about 54% were aged between 18 and 35 years, with a total prevalence in females, 90%. It was evidenced that the clinical picture is quite varied, with a predominance of mutism (75%), immobility/stupor (55%), rigidity (40%) and waxy flexibility (40%). 46% of patients had central nervous system alterations detected by brain magnetic resonance imaging, cranial computed tomography, electroencephalogram or lumbar puncture. Regarding the treatment proposed to each patient, with a description of improvement, the use of benzodiazepines, electroconvulsive therapy, glucocorticoids and immunosuppressants are responsible for almost all the resolution responses. It is concluded that psychiatric disorders are not well described in SLE. This study highlights the importance of diagnosing and treating psychiatric disorders, especially catatonic syndrome. SLE should therefore be included in the differential diagnosis of patients presenting with catatonic syndrome.